Hubungan faktor-faktor pembangunan kerjaya di kalangan pekerja sokongan dengan kepuasan kerja. - Burhan, Bin Bujang. (Universiti Malaysia Sarawak (UNIMAS), 2004)
The research aims to identifY the relationship between work satisfactions with career development factors that influence it. This survey was built based on 50 sample of Medical Assistant that been selected randomly from Kuching and Samarahan areas. During the survey, the researcher uses questionnaire method to acquire the information that been needed. From the result, it J s shown that the level of work satisfaction was on the highest level. Beside that, the result also shows that the work satisfaction ofMedical Assistant was influenced by invigilation, organization policies and self-awareness factor. The related between of that factors can been influenced and should take seriously ifto increase the level ofwork satisfaction. So, the fin ding of the research answers all the problems that identifY how far the work can influences the work satisfaction among the sample that been selected .